GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN KINERJA GURU - Idawati, Idawati (Pascasarjana Universitas Negeri Makassar, 2013)
This a type of comparative technique survey. The population was entire teacher of SD Negeri in Somba Opu Sub Regency of Gowa Regency as much 641 teachers. The sample was taken by using proportional random sampling from the population as much 75 teachers lead by head minister and 77 teachers lead by headmistress, and the differentiation was by using questionnaire in likers scala and then it was analyzed descriptively and statistically by using the analysis of t-test. The result identity that; (i) leadership style of head minister show that he is more authoritative, democratize, laissez faire, and have more charisma than the headmistress; (ii) the headmistress was tend to implement the transformative style in leading; (iii) teachers’ performance lead by head minister and head mistress was show a good category in designing the lesson program, designing the lesson, implementing the lesson process, assessing and evaluating the learning achievement; (iv) there were differentiation between head minister and headmistress in their leadership style. The head minister is more authoritative, democratizes, laissez faire, and has more charisma than the headmistress who is tend to implement the transformative style; (v) there is no differentiation between teachers’ performance lead by head minister and lead by headmistress. Both of then show a good category.